GE_GERICHTE PM/160/2017 vom 10. März 2017 - GE Cour de justice (2017)
ORDONNANCE PÉNALE ; PEINE PÉCUNIAIRE ; CONVERSION DE LA PEINE ; TRAVAIL D'INTÉRÊT GÉNÉRAL ; COMPÉTENCE ; PROCÉDURE | CPP.363.1; CPP.363.2; CP.36.3